(untitled) (The Science Post, 2025)
Polypharmacy is pervasive in outpatient care and increases the risk of adverse drug events (ADEs), drug–drug interactions (DDIs), and nonadherence driven by regimen complexity and cost. This paper proposes an integrated framework for polypharmacy optimization that couples evidence-based deprescribing, CDSS-enabled interaction screening, and patient-centered counseling to simplify regimens while safeguarding outcomes. Using a mixed- methods design, we evaluate changes in medication regimen complexity (MRCI), clinically significant DDI rates, adherence by daily dose burden, and ADE incidence. Results show meaningful reductions in MRCI and DDI rates, improved adherence when daily doses are reduced, and lower ADEs post-intervention. We conclude that aligning deprescribing protocols (STOPP/START, Beers, MAI) with algorithmic checks and shared decision-making can materially improve safety, adherence, and equity in outpatient pharmacotherapy.